The Embeddedness of Depression in the Simple Keynesian Model - Konar, Arup Kanti (Arthshastra Indian Journal of Economics & Research, 2022)
The sole objective of this very short paper was to disclose that depression is ingrained in the simple Keynesian model of hydraulic Keynesianism. Depression occurs in the Simple Keynesian Model because of the fact that the rate of change (growth) of saving is greater than the rate of change (growth) of investment. Depression can be cured, or prosperity can be realized if the rate of change (growth) of saving is equal to or less than the rate of change (growth) of investment.